Folding of an MHC class II-restricted tumor antigen controls its antigenicity via MHC-guided processing. - Mimura, Y; Mimura-Kimura, Y; Doores, K; Golgher, D; Davis, B; Dwek, R; Rudd, P; Elliott, T (2007)
CD4(+) and CD8(+) T cell responses to endogenous retroviral envelope glycoprotein gp90 generate protective immunity to murine colon carcinoma CT26. A panel of I-A(d)-restricted T cell hybridomas recognize gp90 synthesized by CT26 cells but not by other gp90-expressing tumors. Here we report that antigenicity resides in an incompletely folded form of gp90 that is unique to CT26. In contrast to more compact forms of gp90 that are present in other tumors, this open conformer is captured by recycling I-A(d) on antigen-presenting cells and is processed intracellularly. Thus, gp90 acquires immunodominance via MHC-guided processing, and the generation of an MHC class II-restricted response can be controlled by the intracellular folding environment of antigen-expressing cells.